Role of HIV exposure and infection in relation to neonatal GBS disease and rectovaginal GBS carriage: a systematic review and meta-analysis. Issue 1 (December 2017) - Cools, Piet; Wijgert, Janneke; Jespers, Vicky; Crucitti, Tania; Sanders, Eduard; Verstraelen, Hans; Vaneechoutte, Mario
Abstract Streptococcus agalactiae (GBS) is the leading cause worldwide of neonatal sepsis. We sought to assess to which extent HIV exposure of neonates is associated with GBS neonatal disease. Furthermore, we assessed to which extent HIV infection in women is associated with maternal rectovaginal GBS carriage, the single most important risk factor for GBS neonatal disease. We searched Pubmed, Embase, and Web of Science for studies assessing the association between neonatal GBS disease and HIV-status of the mother and studies that assessed the association between rectovaginal GBS colonization and HIV status in women. HIV-exposed uninfected neonates were more than twice as likely to have neonatal GBS disease compared to unexposed neonates. HIV-exposed neonates were not at increased risk for early-onset neonatal disease, but were 4.43 times more likely to have late-onset neonatal GBS disease. There was no significant association between HIV infection status and rectovaginal GBS carriage. Public health interventions preventing neonatal GBS disease are urgently needed for the increasing group of HIV-exposed neonates. A framework integrating and explaining our findings highlights opportunities for the clinical practice and global health policy to prevent disease. Well-designed studies should clarify the relation between HIV-status and GBS carriage.